Outcomes and treatments of patients with immunoglobulin light chain amyloidosis who progress or relapse postautologous stem cell transplant. (2nd March 2014) - Warsame, Rahma; Bang, Soo Mee; Kumar, Shaji K.; Gertz, Morie A.; Lacy, Martha Q.; Buadi, Francis; Dingli, David; Hayman, Suzanne R.; Kapoor, Prashant; Kyle, Robert A.; Leung, Nelson; Lust, John A.; et al.
Abstract Immunoglobulin light chain (AL) Amyloidosis is a condition whereby misfolded proteins generated by plasma cells deposit in tissues causing organ dysfunction. Chemotherapy and autologous stem cell transplant when eligible are standard treatment options. Several studies report long‐term outcomes of patients post‐transplant. However, there is a paucity of literature describing outcomes of relapsed patients post‐transplant. We performed a retrospective study to assess outcomes and therapies employed upon relapse after transplant. Between 1996 and 2009, 410 patients received transplant at the Mayo Clinic as first‐line therapy. Of those patients, 42 (10%) died within 3 months of transplant, 64 (16%) died without documented relapse, 158 (38%) were alive without documented progression, and 146 (36%) had documented progression. Those 146 patients are the subject of our study, and their median time to hematologic relapse/progression was 23.6 months (95%CI 18.3, 26.3 months). Their median overall survival and 5‐yrs overall survival from post‐transplant relapse/progression was 51.7 months (95%CI 34.1–62.3) and 39%, respectively. The most common first regimen for treatment after relapse was lenalidomide or thalidomide. In conclusion, our study indicates that patients with AL amyloidosis fare well post‐transplant relapse/progression. Additionally, it provides a yardstick to design clinical trials to determine best treatment options.